1987
DOI: 10.1056/nejm198702053160601
|View full text |Cite
|
Sign up to set email alerts
|

Maturity-Onset Diabetes of Youth in Black Americans

Abstract: Twelve of 129 black patients with youth-onset diabetes were identified as having an unusual clinical course, with apparent insulin dependence at the time of presentation followed by absence of dependence months to years later. This atypical form of diabetes was found in at least two generations in 9 of the 12 families of the propositi. Fourteen of the diabetic relatives, as well as the 12 propositi, were studied. Islet-cell autoantibodies were not found in any of the patients, and thyroid microsomal auto-antib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
142
1
9

Year Published

1997
1997
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 240 publications
(160 citation statements)
references
References 57 publications
8
142
1
9
Order By: Relevance
“…And they exhibited type 2 DMclinical course after presenting with DKA.This unusual form of diabetes has been recognized in African-Americans and Japanese (4-7). Winter et al (15) reported that some young Afri- can-Americans mayhave symptomsof insulin deficiency, with or without ketoacidosis, but display clinical and metabolic features of type 2 diabetes. Obesity was present in 50%of their patients.…”
Section: Discussionmentioning
confidence: 99%
“…And they exhibited type 2 DMclinical course after presenting with DKA.This unusual form of diabetes has been recognized in African-Americans and Japanese (4-7). Winter et al (15) reported that some young Afri- can-Americans mayhave symptomsof insulin deficiency, with or without ketoacidosis, but display clinical and metabolic features of type 2 diabetes. Obesity was present in 50%of their patients.…”
Section: Discussionmentioning
confidence: 99%
“…However, DKA may occur at presentation in subjects who are eventually found to have type 2 diabetes (38); that is, they have elevated C-peptide and an absence of antibodies to islet cells (ICA) or glutamic acid decarboxylase (anti-GAD), and after the initial period of severe metabolic disturbance, they do not require insulin (13). Initial reports were among African-American adults, and an autosomal dominant inheritance was suggested (38,39). Subsequent studies have confirmed that type 2 diabetes often presents with ketosis or DKA and occurs in ϳ40% of African-American children (40,41) with type 2 diabetes, 4% of children with Canadian aboriginal backgrounds (42), and 30% of children with Mexican-American backgrounds (32).…”
Section: Complications-morbidity and Mortalitymentioning
confidence: 99%
“…amplification of allelic effect in the presence of variants at other loci, is likely to be present further illustrating the complexity. The prevalent Ala allele of the Pro12Ala polymorphism of the peroxisome proliferator-activated receptor-γ (PPAR-γ) gene is associated in many studies with increased insulin sensitivity and a decreased risk of Type 2 diabetes [1]. In line with these observations, we recently showed an association of the Ala/Ala genotype and a decreased propensity to develop the IRS in the Danish Monitoring of trends and determinants in Cardiovascular diseases (MONICA) study population [2].…”
mentioning
confidence: 54%
“…To the Editor: Type 1B diabetes or ketosis-prone atypical diabetes (KPAD) is a subtype of diabetes mostly described in patients of sub-Saharan African ancestry and characterized by insulin dependence at the time of presentation, without immunological markers seen in typical Type 1A diabetes (T1D), and frequently followed by absence of insulin requirements as in the case of Type 2 diabetes (T2D) [1,2,3]. The subsequent clinical course of KPAD, which could represent up to 12% of the sub-Saharan African diabetic population, is characterized by an alternance of near normoglycaemic remissions and relapses of insulin dependence without precipitating illness [3,4].…”
mentioning
confidence: 99%